2007
DOI: 10.1007/s10620-007-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Perineural Invasion Following Pancreatoduodenectomy With Lymphadenectomy for Ampullary Carcinoma

Abstract: The aim of this study was to identify prognostic factors in patients undergoing pancreatoduodenectomy with lymphadenectomy for ampullary carcinoma. The records of 46 consecutive patients with ampullary carcinoma who underwent pancreatoduodenectomy from 1988 through 2006 were retrospectively reviewed. A 98% rate of potentially curative (R0) resection was achieved. There was no 30-day mortality. Overall 5-year survival rate was 64%. Univariate analysis revealed that T3 and T4 tumor (i.e., pancreatic parenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
2
26
1
1
Order By: Relevance
“…Perineural invasion extending into the pancreatic nerve plexus is a histopathological characteristic of pancreatic cancer [5,31]. The frequent infiltration of pancreatic cancer cells in nerves has been noted for a long time, and some data indicate that, in pancreatic cancer patients, the perineural invasion is significantly associated with the prognosis [32][33][34]. However, the mechanisms that contribute to the invasion of pancreatic nerves are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion extending into the pancreatic nerve plexus is a histopathological characteristic of pancreatic cancer [5,31]. The frequent infiltration of pancreatic cancer cells in nerves has been noted for a long time, and some data indicate that, in pancreatic cancer patients, the perineural invasion is significantly associated with the prognosis [32][33][34]. However, the mechanisms that contribute to the invasion of pancreatic nerves are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although PNI is a relatively common feature in a variety of human malignancies, as in adenoid cystic and squamous cell sinunasal cancers, pancreatic and prostatic carcinomas with prognostic impact (Gil et al 2009;Harnden et al 2007;Lee et al 2007;Sudo et al 2008), little research attention has been paid to this parameter. In carcinoma of the cervix uteri (CX), the vast majority of studies dealing with prognostic factors do not cover PNI in their analyses (Morice et al 1999;Pieterse et al 2008;Sartori et al 2007;Takeda et al 2002;Trimbos et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Potential factors include surgical margin status [26,27], nodal involvement [4,26,[28][29][30][31], pancreatic invasion [30,31], and perineural invasion [8,32,33]. Moreover, prognostic significance of several molecular markers has been reported using immunohistochemical staining [28,31,34].…”
Section: Discussionmentioning
confidence: 99%
“…Ampullary carcinoma generally has a better prognosis as well as resectability, than pancreatic or distal bile duct carcinomas [3]. Recent retrospective series have shown that 5-year survival rates ranged from 63% to 84% for patients with lymph node-negative disease and from 19% to 29% for node-positive disease in patients who underwent pancreaticoduodenectomy for ampullary carcinoma [4][5][6][7][8]. The prognosis with advanced-stage ampullary carcinoma patients remains still poor.…”
Section: Introductionmentioning
confidence: 99%